The inclusion of ethical competencies in the framework of political science: A pilot experience based on project-based learning - Pardo Beneyto, Gonzalo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The main objective of this article is to present the main results of a teaching innova- tion experience implemented in the 4th year of the Double Degree Program in Law and Political Science and Administration at the University of Valencia (UV). Specifi- cally, the teacher proposed a series of cards in which measures were proposed to put an end to corruption. This activity took place during the months of April and May 2022. In order to measure prior knowledge and carry out a subsequent evaluation, an initial and final surveys were launched.